Evaluation of dynamic response characteristics of seismically isolated bridges in Chile. - Sarrazin, Mauricio (Earthquake engineering & structural dynamics.)
A complete renovation of the Pan-American Highway from La Serena to Puerto Montt, Chile, has been recently completed, including the construction of several long-span bridges, with different structural systems. Most of them have some sort of seismic protection, such as high-damping rubber bearings, friction bearings or energy dissipation devices. Ambient vibration tests have been conducted on seven of these bridges to obtain their natural frequencies, modes of vibration, and equivalent damping, under small amplitude vibrations. In two of them local accelerometer networks have been installed for continued monitoring of their seismic behavior and a number of earthquakes have already been recorded. The seismic records show clearly the beneficial effect of the isolation and energy dissipation devices in the longitudinal direction. Analytical models with different degrees of complexity have been developed to reproduce the recorded behavior under ambient vibration and moderate earthquakes. This paper presents some of the data obtained and summarizes the research done by the authors over the last 10 years at the University of Chile on the seismic protection of bridges.